2011
DOI: 10.1007/s10661-011-2149-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and multiple sources of heavy metals in the water of Chaohu Lake, Anhui, China

Abstract: In this study, a survey for the spatial distribution of heavy metals in Chaohu Lake of China was conducted. Sixty-two surface water samples were collected from entire lake including three of its main river entrances. This is the first systematic report concerning the content, distribution, and origin of heavy metals (Cu, Cr, Cd, Hg, Zn, and Ni) in the Chaohu Lake water. The results showed that heavy metals (Cu, Cr, Zn, and Ni) concentrations in the estuary of Nanfei River were relatively higher than those in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 35 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…When analyzing the background levels of the sampling sites, the water samples that contained heavy metals in PC 1 and PC 3 often occurred in samples from irrigation channels, rivers and lakes near the townships of the central Urumqi-Akesu and the eastern part of the Balikun-Yiwu sections. Previous studies have shown that heavy metals, such as Zn, Hg, and Mn, are often contained in the emissions from urban and industrial areas and activities (Erdem et al 2004;Karbassi et al 2008;Delgado et al 2010;Kurun et al 2010;Li et al 2012). The water samples that contained a high concentration of heavy metals in PC 2 were often taken from the rivers, lakes, and streams in the mountains and wilderness areas contaminated by little human activity.…”
Section: Correlation Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…When analyzing the background levels of the sampling sites, the water samples that contained heavy metals in PC 1 and PC 3 often occurred in samples from irrigation channels, rivers and lakes near the townships of the central Urumqi-Akesu and the eastern part of the Balikun-Yiwu sections. Previous studies have shown that heavy metals, such as Zn, Hg, and Mn, are often contained in the emissions from urban and industrial areas and activities (Erdem et al 2004;Karbassi et al 2008;Delgado et al 2010;Kurun et al 2010;Li et al 2012). The water samples that contained a high concentration of heavy metals in PC 2 were often taken from the rivers, lakes, and streams in the mountains and wilderness areas contaminated by little human activity.…”
Section: Correlation Analysismentioning
confidence: 99%
“…Related literatures suggest they are mainly derived from the natural geological background from rock weathering, dry river floods, etc. Thus, under the power of rains and floods, Co, Cr, As, and Ni can be transferred to bodies of water, such as streams, rivers, and lakes (Qi et al 2002;Karbassi et al 2008;Li et al 2008Li et al , 2012Adhikari et al 2009;Zhang et al 2011;Hu et al 2012). …”
Section: Correlation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Zhang et al (2005) found As contents in plant tissues to be 3.5 times higher in the polluted area than the non-polluted area within the study area. The As is mainly from swine factory (Peng et al, 2014), agriculture fertiliser input (Li et al, 2012), or mining industry (Zhang et al, 2005). Similar research shows that As in Daye Lake is mainly from human activities particularly mining industries (Zhang et al, 2006).…”
Section: Spearman Correlation and Multivariate Analysis 331 Spearmamentioning
confidence: 99%